Willingness to Pay for Environmental Services in Bendung Lepen Community-Based Agro-Tourism (A Contingent Valuation Approach) - Fadiilla Ristya Aminda; Dinda Dewi Aisyah (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2025)
Ecosystem service valuation is essential for revealing the real benefits of community-based agro-tourism. It helps communities link environmental sustainability with local economic gains. Hence, this study aims to apply the Contingent Valuation Method, particularly Willingness to Pay (WTP), to capture the local community's views on improving ecosystem services in Bendhung Lepen. A total of 41 residents were used as the sample for this study. Then, we identify the factors that influence WTP. Multiple linear regression was used to analyze these factors. The analysis results show that the average WTP of the local community is IDR 8,414.63 per person. In addition, this study found that levels of education, the number of family members, and knowledge of ecosystem benefits significantly influence the amount of WTP for improving ecosystem services in Bendhung Lepen. The number of family members and education level have a significant adverse effect on WTP, while knowledge has a significant positive effect. The greater the number of family members and the higher the level of community education, the lower the WTP value. On the other hand, communities with higher knowledge of environmental conditions have been shown to have a higher WTP than those without. This finding implies that the local community has not fully supported efforts to improve ecosystem services in the area. Also, it provides insights for developing sustainable funding mechanisms and environmental education strategies in community-based agro-tourism. Institutional support can be provided to educate residents so they can achieve a similar level of environmental knowledge and awareness.